1990
DOI: 10.1051/animres:19900101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of milking method and post-milking suckling on ewe milk production and lamb growth

Abstract: Summary — The effects of milking method (machine milking, machine milking and hand stripping, hand milking) and of post-milking suckling on milk yield and milk fat percentage of Chios ewes were investigated in 2 separate trials over a 5-wk period following weaning at 6 wks of age. The effects of post-milking suckling and creep feeding versus creep feeding alone on the growth of lambs were also examined over the same period. Differences in the commercial milk (kg per ewe over the experimental period) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
3
12
0
6
Order By: Relevance
“…Consequently, milking machine captured their cisternal milk but not alveolar milk, in which most of fat is present. Papachristoforou (1990) reported that Chios ewes suckled by their lambs showed some ability to withhold a certain amount of milk which is released only when ewes are stimulated by the presence of lambs. This author studied fat percentages in ewes of various lamb rearing systems between day 43 and day 77 after parturition; these were found higher in machine milked ewes permanently separated from their lambs than in machined (or hand) milked ewes suckled by their lambs for 5 to 10 min, having audiovisual (i.e., no direct) contact with offspring.…”
Section: Milk Yield and Milk Composition Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, milking machine captured their cisternal milk but not alveolar milk, in which most of fat is present. Papachristoforou (1990) reported that Chios ewes suckled by their lambs showed some ability to withhold a certain amount of milk which is released only when ewes are stimulated by the presence of lambs. This author studied fat percentages in ewes of various lamb rearing systems between day 43 and day 77 after parturition; these were found higher in machine milked ewes permanently separated from their lambs than in machined (or hand) milked ewes suckled by their lambs for 5 to 10 min, having audiovisual (i.e., no direct) contact with offspring.…”
Section: Milk Yield and Milk Composition Traitsmentioning
confidence: 99%
“…Some benefits in terms of lamb growth intensity (Papachristoforou, 1990) in mixed treatment was reported, nevertheless, extra labour involved and stress on mother/offspring of joining and separating, together with an effect on milk fat should be taken into account when deciding whether this treatment is introduced. Peters and Heaney (1974) reported that difference between weights of lambs not separated from ewes and lambs separated from ewes at age of 35 days was significant (i.e., not separated lambs made better gains at early life than separated lambs).…”
Section: Lamb Growth Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mixed systems for early lactation management of ewes allowing both suckling and milking were also reported (Papachristoforou, 1990;McKusick et al, 2001). During the first 30 days of lactation a dairy ewe produces quite an important amount of total lactation milk yield (Folman et al, 1966); it is the period when lambs are typically allowed to suckle their dams.…”
mentioning
confidence: 99%
“…A positive effect of the presence of the calf on PRL release has also been reported in nursing cows by Perez et al (1985), although not by others (Akers and Lefcourt, 1984). In small dairy ruminants, maintaining some mother-young interaction during lactation also appears to have beneficial effects on milk production: when milking is combined with restricted mother-young contact in goats and sheep, it does not significantly reduce the quantity of milk obtained by milking (Folman et al, 1966;Morag et al, 1970;Hadjipanayiotou, 1985;Papachirtoforou, 1990;Peris et al, 1997), and can even lead to a higher milk collection (Hadjipanayiotou and Louca, 1976). However, to our knowledge the possible beneficial consequences of maintaining some mother-young contact on milk production in goats, when the udder is emptied by milking only once daily, have not been investigated in previous research.…”
Section: Introductionmentioning
confidence: 92%